A comparative review of measurement instruments to inform and evaluate effectiveness of disability inclusive development. (May 2014) - Goujon, Nicolas; Devine, Alexandra; Baker, Sally M.; Sprunt, Beth; Edmonds, Tanya J.; Booth, Jennifer K.; Keeffe, Jill E.
Abstract Purpose: A review of existing measurement instruments was conducted to examine their suitability to measure disability prevalence and assess quality of life, protection of disability rights and community participation by people with disabilities, specifically within the context of development programs in low and middle-income countries. Methods: From a search of PubMed and the grey literature, potentially relevant measurement instruments were identified and examined for their content and psychometric properties, where possible. Criteria for inclusion were: based on the WHO's International Classification of Functioning Disability and Health (ICF), used quantitative methods, suitable for population-based studies of disability inclusive development in English and published after 1990. Characteristics of existing instruments were analysed according to components of the ICF and quality of life domains. Results: Ten instruments were identified and reviewed according to the criteria listed above. Each version of instruments was analysed separately. Only three instruments included a component on quality of life. Domains from the ICF that were addressed by some but not all instruments included the environment, technology and communication. Conclusion: The measurement instruments reviewed covered the range of elements required to measure disability-inclusion within development contexts. However no single measurement instrument has the capacity to measure both disability prevalence and changes in quality of life according to contemporary disability paradigms. The review of measurement instruments supports the need for developing an instrument specifically intended to measure disability inclusive practice within development programs. Implications for Rehabilitation Surveys and tools are needed to plan disability inclusive development. Existing measurement tools to determine prevalence of disability, wellbeing, rights and access to the community were reviewed. No single validated tool exists for population-based studies, uses quantitative methods and the components of the ICF to measure prevalence of disability, well-being of people with disability and their access to their communities. A measurement tool that reflects the UNCRPD and addresses all components of the ICF is needed to assist in disability inclusive development, especially in low and mid resource countries.